A bivalent B‐cell epitope dendrimer peptide can confer long‐lasting immunity in swine against foot‐and‐mouth disease. Issue 4 (12th February 2020) - Cañas‐Arranz, Rodrigo; Forner, Mar; Defaus, Sira; Rodríguez‐Pulido, Miguel; de León, Patricia; Torres, Elisa; Bustos, María J.; Borrego, Belén; Sáiz, Margarita; Blanco, Esther; Andreu, David; Sobrino, Francisco
Abstract: Foot‐and‐mouth disease virus (FMDV) causes a widely extended contagious disease of livestock. We have previously reported that a synthetic dendrimeric peptide, termed B2 T(mal), consisting of two copies of a B‐cell epitope [VP1(140–158)] linked through maleimide groups to a T‐cell epitope [3A(21–35)] of FMDV, elicits potent B‐ and T‐cell‐specific responses and confers solid protection in pigs to type O FMDV challenge. Longer duration of the protective response and the possibility of inducing protection after a single dose are important requirements for an efficient FMD vaccine. Herein, we show that administration of two doses of B2 T(mal) elicited high levels of specific total IgGs and neutralizing antibodies that lasted 4–5 months after the peptide boost. Additionally, concomitant levels of IFN‐γ‐producing specific T cells were observed. Immunization with two doses of B2 T(mal) conferred a long‐lasting reduced susceptibility to FMDV infection, up to 136 days (19/20 weeks) post‐boost. Remarkably, a similar duration of the protective response was achieved by a single dose of B2 T(mal). The effect on the B2 T(mal) vaccine of RNA transcripts derived from non‐coding regions in the FMDV genome, known to enhance the immune response and protection induced by a conventional inactivated vaccine, was also analysed. The contribution of our results to the development of FMD dendrimeric vaccines is discussed.